iOS cloud development for dummies - Goldstein, Neal. (Laura Ann); 1906-1998.; 1970- (Hoboken, NJ. Wiley, 2012)
Build robust, data-driven mobile apps and web services that take advantage of iCloud. This guide will help you create apps that share data, keep that data current, sync it with iCloud, and more-- |c Source other than Libary of Congress.
Includes index.
Keywords: Web services; Application software -- Development; Cloud computing; iOS (Electronic resource)